Tlingit totem poles in graveyard, Tuxekan, Prince of Wales Island, Alaska, ca. 1904 - Case, W. H. (William Howard), 1868-1920
11 Tlingit totem poles in graveyard, Prince of Wales Island, Alaska, ca. 1898-1910. Nine are free-standing, two are part of tomb structures. Same totems in NA2457. Caption on image: Totems at Old Tuxekan. Notes from unidentified sources: On west coast of Prince of Wales Island, Henya tribe of Tlingit. PH Coll 300.35